Edukasi Gizi Sarapan Pagi Anak Sekolah SDN 07 Kramat Pela Jakarta Selatan - Meilinasari; Rosmida M. Marbun; Anastu Regita Nareswara; Ns. Paula Krisanty (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Breakfast is a eating activity that is consumed in the morning, which is less than 1/3 of the food consumed in a day with the required calorie range of 300-500 Kcal. Based on data from Basic Health Research (Riskesdas) in 2018, as many as 26% of Indonesian children only consume drinks such as water, milk, and tea at breakfast time. Knowledge and attitude are one of the factors that influence children to eat breakfast. Efforts that can be made to improve children's knowledge are by providing education. This service activity aims to increase the understanding of students of SDN 07 Kramat Pela, South Jakarta, about breakfast activities. The educational media used includes animated videos, posters and leaflets. The evaluation of the education provided was measured using pretest and posttest questionnaires. The results show. There was a consistent result of knowledge in the good category of 97.0% in the pretest and posttest scores. The pretest results showed 3.0% in the less category, and in the posttest results there were no results in the less category.